Immobilized enzyme using a mica carrier - Abdul Rahman, Mohd Basyaruddin; Zaidan, Uswatun Hasanah; Basri, Mahiran; Salleh, Abu Bakar; Othman, Siti Salhah; Raja Abdul Rahman, Raja Noor Zaliha (2010)
The present invention provides a novel immobilized lipase having a mica carrier. Accordingly, the present invention attempts to choose and use a low cost mica clay from the local resource for lipase immobilization. The use of powder mica treated by calcinations has shortened the processing of enzyme carrier preparation, thus minimizing the cost of carrier itself. Immobilization of lipase onto the calcined mica with nano-size of pore diameter (<50 nm) has been done through a simple physical adsorption method where the lipase solution was directly added to the solid calcined mica by continous agitation at 100 rpm for 2 hours. Then, a small volume of gluteradehyde solution was added into the mica-lipase solution to allow the lipase molecules inside the nanoporous channel of mica to be cross-linked to each other for the purpose of leaching prevention effect. Finally, the lipase-loaded mica (immmobilized lipase) was filtered from the solution before being dried in a freeze dryer.